1999
DOI: 10.1046/j.1464-410x.1999.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

MN/CA9 gene expression as a potential biomarker in renal cell carcinoma

Abstract: These results suggest that MN/CA9 expression is a potential diagnostic biomarker of RCC, especially the clear-cell type, and can be targeted using molecular biological techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 15 publications
5
17
0
1
Order By: Relevance
“…Again with high tumor grade there was a high rate of low expression (81.8%). These outcomes are again consistent with the previous literature [10][11][12]14]. When the cumulative survival rate was correlated with the tumor grade, stage and CA9 expression, CA9 expression was at least as good a factor effecting survival rate as T stage and tumor grade.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Again with high tumor grade there was a high rate of low expression (81.8%). These outcomes are again consistent with the previous literature [10][11][12]14]. When the cumulative survival rate was correlated with the tumor grade, stage and CA9 expression, CA9 expression was at least as good a factor effecting survival rate as T stage and tumor grade.…”
Section: Discussionsupporting
confidence: 92%
“…In the CCC group, the staining rate was 91%. Murakami et al [10] found CA9 expression in CCC to be 92%; this rate in the paper by Bui et al [15] was reported to be 94%.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…CA-IX is an HIF-a target gene that is frequently expressed in RCC but very rarely detected in normal kidney tissue (27). We observed an overexpression of CA-IX in all but one ccRCC samples.…”
Section: Discussionmentioning
confidence: 59%
“…17 Of these enzymes, CA IX is a membrane bound version and its over-expression on the cell surface is seen in a number of solid tumors, particularly in clear cell RCC and including cervical, ovarian, colorectal, head and neck, bladder and non-small cell lung carcinomas. 18,19 In all these malignancies, the expression of CA IX is invariably linked to the development of tumor hypoxia which is mediated by the transcription factor HIF-1.…”
Section: Introductionmentioning
confidence: 99%